An Acellular Scaffold Facilitates Endometrial Regeneration and Fertility Restoration via Recruiting Endogenous Mesenchymal Stem Cells. Issue 21 (9th September 2022) - Xin, Liaobing; Zheng, Xiaowen; Chen, Jianmin; Hu, Sentao; Luo, Yilun; Ge, Qunzi; Jin, Xiaoying; Ma, Lie; Zhang, Songying
Abstract: Severe intrauterine adhesions (IUAs), characterized by inadequate endometrial repair and fibrosis, can lead to infertility. Stem cell‐based therapies, which deliver mesenchymal stem cells (MSCs) to the wound site, hold a considerable promise for endometrium regeneration. However, some notable hurdles, such as stemness loss, immunogenicity, low retention and survival rate, limit their clinical application. Evidence shows a strategy of mobilizing endogenous MSCs recruitment can overcome the traditional limitations of exogenous stem cell‐based therapies. Here, an acellular biomaterial named stromal derived factor‐1 alpha (SDF‐1 α )/E7‐modified collagen scaffold (CES) is explored. CES based on harnessing the innate regenerative potential of the body enables near‐complete endometrium regeneration and fertility restoration both in a rat endometrium acute damage model and a rat IUA model. Mechanistically, the CES implantation promotes endogenous MSCs recruitment via a macrophage‐coordinated strategy; then the homing MSCs exert the function of immunomodulation and altered local microenvironments toward regeneration. To conclude, CES, which can harness endogenous MSCs and overcome the traditional limitations of cell‐based therapies, can serve as a clinically feasible and cell‐free strategy with high therapeutic efficiency for IUA treatment. Abstract : An acellular stromal derived factor‐1 alpha (SDF‐1 α )/E7‐modified collagen scaffold (CES) is designed to treat intrauterine adhesions (IUAs) in rodent models. After CES implantation, endometrial repair and fertility restoration can be achieved. In mechanism, the CES implantation can promote endogenous MSCs' recruitment via a macrophage‐coordinated strategy, and the homing MSCs can reciprocally exert immunomodulation on the phenotype of macrophages.